Night shift work and breast cancer risk: what do the meta-analyses tell us? - Pahwa, Manisha; Labrèche, France; Demers, Paul A. (Scandinavian Journal of Work, Environment & Health, 2018)
' ' OBJECTIVES ': 'This paper aims to compare results, assess the quality, and discuss the implications of recently published meta-analyses of night shift work and breast cancer risk. ' ' METHODS ': 'A comprehensive search was conducted for meta-analyses published from 2007–2017 that included at least one pooled effect size (ES) for breast cancer associated with any night shift work exposure metric and were accompanied by a systematic literature review. Pooled ES from each meta-analysis were ascertained with a focus on ever/never exposure associations. Assessments of heterogeneity and publication bias were also extracted. The AMSTAR 2 checklist was used to evaluate quality. ' ' RESULTS ': 'Seven meta-analyses, published from 2013–2016, collectively included 30 cohort and case–control studies spanning 1996–2016. Five meta-analyses reported pooled ES for ever/never night shift work exposure; these ranged from 0.99 [95% confidence interval (CI) 0.95–1.03, N=10 cohort studies) to 1.40 (95% CI 1.13–1.73, N=9 high quality studies). Estimates for duration, frequency, and cumulative night shift work exposure were scant and mostly not statistically significant. Meta-analyses of cohort, Asian, and more fully-adjusted studies generally resulted in lower pooled ES than case–control, European, American, or minimally-adjusted studies. Most reported statistically significant between-study heterogeneity. Publication bias was not evident in any of the meta-analyses. Only one meta-analysis was strong in critical quality domains. ' ' CONCLUSIONS ': 'Fairly consistent elevated pooled ES were found for ever/never night shift work and breast cancer risk, but results for other shift work exposure metrics were inconclusive. Future evaluations of shift work should incorporate high quality meta-analyses that better appraise individual study quality.
Keywords: breast cancer; cancer; hazard assessment; literature review; meta-analysis; night shift; night shift work; review; risk assessment; shift work; short communication